Daylighting Performance in Balai Padang Adat House at South Borneo - Febby Rahmatullah Masruchin; I Gusti Ngurah Antaryama; Sri Nastiti N. Ekasiwi; Desak Putu Damayanti (Institut Teknologi Sepuluh Nopember, 2017)
Balai Padang Adat is one of the traditional building in tropical area. The characteristic of this building is large, long and deep dimention but it has limited area of the openings. Field meassurement for 3 days and 3 times (09.00, 12.00, 15.00) is used to identify factors that affect daylighting performance. This research found that daylighting performance was in poor quality. The outdoor illumination is very high which reached 100.000 lux caused by latitude, altitude and cloud cover. The latitude is 2o in the south from the equator’s line and the altitude is 450 meters above sea level which close from the sun. The cloud cover is minimum lower than 40%. The indoor illumination can reach 1 lux as the lowest level during the day caused by obstruction, overhang, shape and space of the building, material reflectance, area and position of the openings. There is a building in the west and east and a vegetation in the south as an obstruction. This building has a large dimention with double layer room, but it has minimum material reflectance of the wall and floor. This building has a minimum area of the openings, high position of the openings near the overhangs and also long dimention of the overhang. Meassurement was done in Laras-Pematang room as a living room and Bilik room as a bedroom and kitchen. Overall, daylighting performance of this building can not meet standart activity such as illumination value, daylighting factors and daylighting distribution from morning to the evening.